Comparison between Pure-tone Audiometry and Otoacoustic Emissions Methods in Workers’ Hearing Loss - Dehaghi, Behzad Fouladi (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Noise-induced hearing loss (NIHL) is the most important physiological effect of noise that is the mechanical deterioration of outer hair cells in the organ of Corti. The study aim was to a comparison between pure-tone audiometry (PTA) and distortion product otoacoustic emissions (DPOAEs) methods in workers’ hearing loss. Materials and Methods: A total of 120 workers were enrolled in the study, who worked in two production units of a company. Workers exposed to high levels of noise were divided into two groups of with NIHL and without NIHL. Then, their hearing status was evaluated using PTA and DPOAEs tests. Results: The results revealed a tangible difference between data obtained from PTA and DPOAEs methods between two groups and workers with normal hearing threshold experienced a high reduction in their DPOAEs range. This indicates a reduction in the number of outer hair cells of cochlea which is not detectable by PTA test. Conclusion: This study represents that DPOAEs can detect NIHL at earlier steps compared to PTA test. Therefore, it is recommended to use DPOAEs test in industrial environments for hearing screening test and early diagnosis of NIHL, instead of PTA.